Environmental sustainability through participatory approaches : socio-geographic assessment of the Mathenjwa tribal authority landscape, Northern KwaZulu-Natal - Torquebiau, Emmanuel (University of Pretoria, 2013)
Dissertation (MA)--University of Pretoria, 2013.